Grandmothers Promote Maternal and Child Health : The Role of Indigenous Knowledge Systems' Managers - Aubel, Judi (World Bank, Washington, DC, 2012)
In virtually all societies, the managers of indigenous knowledge (IK) systems that deal with the development, care and well-being of women and children are senior women, or grandmothers. In that function, grandmothers are expected to advise and supervise the younger generations. However, most development programs neither acknowledge their influence, nor explicitly involve them in efforts to strengthen existing family and community survival strategies. Many discussions of indigenous knowledge tend to be rather narrow, in two respects. First, IK is often presented in terms of specific knowledge and practices, or "nuggets of traditional wisdom" in relative isolation from the community knowledge authorities and systems of which such knowledge is a part. Second, many discussions of IK, point to the beneficial elements of traditional knowledge and practice while completely ignoring the harmful elements. Andreas Fuglesang, Swedish communication for development expert, discussed the central role played by elders in information management in traditional cultures. He described the function of elders as the "information storage and processing unit" of a society, like the hard drive on a computer. He described their critical role in ensuring continuity between the knowledge and values of their forefathers and the needs of younger generations preparing for life in the future. Gender is another important dimension of the management of IK systems. In most societies, many roles are gender-specific, and, therefore, the expertise of elder men and elder women differs. As regards expertise related to the growth and development of young children, and to the well-being of women of reproductive age (WRA), it is clearly senior women, or grandmothers, who have greater experience and greater knowledge. The individual behavior change orientation, widely adopted around the world, tends to focus on WRA while largely ignoring the socio-cultural systems of which they are a part, and in which elder family members play an influential role.